Biolarvacide Leaves Powder of Mimosa Pudica L. on Mortality The Mosquito of Culex quinquefasciatus - Jhon Riswanda; Novi Marisca; Muhammad Fauzi Romadhan (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
This research aims to determine the potential of Mimosa pudica L. as a larvicide for the mosquito of Culex quinquefasciatus. This research used an experimental method with a Completely Randomized Design (CRD), consisting of 6 treatments and 4 replications. The treatments consisted of treatment 0 gr/100 ml (control -); abate 0.4 gr/100 ml (control +); treatment (P1) 0.1 gr/100 ml; treatment (P2) 0.2 gr/100 ml; treatment (P3) 0.3 gr/100 ml; treatment (P4) 0.4 gr/100 ml. The parameter observed in this study was the mortality rate larvae instar III of Culex quinquefasciatus. The analysis used in this research was One Way Anova using a software application, namely SPSS statistics 22. To find out the potential of Mimosa pudica L. on the mortality rate larvae instar III of Culex quinquefasciatus larvae, it can be seen from the significance value. If the significance value is less than 0.01, it means that the treatment has a very significant effect, then further tests will be carried out. The further test used is the Duncan test. From the results of research that have been calculated using the One Way Anova test, it is proven that there is an effect of giving Mimosa pudica L.leaf's powder on mortality larvae instar III of Culex quinquefasciatus. The effect that occurs can be seen in the significance value < 0.01, meaning that the leaves powder of Mimosa pudica L. has a very significant effect on the mortality larvae instar III of Culex quinquefasciatus. It can be concluded that the Mimosa pudica Lhad the potential as biolarvicide of Culex quinquefasciatus. Keywords: Biolarvacide, Larvacide, Mimosa pudica L, Leaves Powder, Culex quinquefasciatus